Zinc electrode for alkaline nickel-zinc battery and preparation method of zinc electrode
By using water-soluble calcium organic acid salts to coat calcium hydroxide and calcium zincate in situ, the problem of zinc oxide dissolution and deformation of zinc electrodes is solved, and the cycle life of alkaline nickel-zinc batteries and electrolyte penetration is significantly improved. It avoids equipment corrosion and quality control difficulties.
Patent Information
- Application Number
- CN202411301831.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Insoluble inorganic calcium salt additives used in the zinc electrodes of alkaline nickel-zinc batteries in the prior art cannot effectively inhibit the dissolution and deformation of zinc oxide of zinc electrodes, resulting in short battery cycle life and difficulty in quality control and equipment corrosion problems in production processes.
The surface of nano zinc oxide or metal zinc powder is coated in situ with water-soluble calcium organic acid salt to form uniform calcium hydroxide and calcium zincate, and the electrochemical reversible calcium zincate is formed on the surface and inside of the zinc electrode through chemical interaction. phase, reduce zinc oxide solubility and inhibit zinc dendrites growth.
It significantly improves the cycle life and discharge capacity of zinc electrodes, improves the permeability of the electrolyte, extends the service life of the battery, and avoids equipment corrosion and quality control difficulties.
Smart Images

Figure CN119297214A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical batteries, and in particular to a zinc electrode for an alkaline nickel-zinc battery and a method for preparing the zinc electrode. Background Art
[0002] This section provides background information related to the present application which does not necessarily constitute prior art.
[0003] Alkaline nickel-zinc batteries are electrochemical energy storage devices containing zinc electrodes. The electrolyte used in alkaline nickel-zinc batteries is an alkaline electrolyte with deionized water as the main solvent. Among them, the zinc electrode, as the negative electrode part of the nickel-zinc battery, mainly undergoes a reversible electrochemical conversion reaction between zinc oxide and metallic zinc. Usually, the zinc electrode is composed of zinc oxide, metallic zinc powder, a binder, a metal element with certain functionality, a metal oxide or a metal hydroxide additive, especially an additive that slows down the dehydrogenation side reaction, controls the deformation of the negative electrode, and inhibits the growth of zinc dendrites. The alkaline electrolyte is mainly composed of an aqueous solution of alkaline electrolytes such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, which mainly provides hydroxide ions to participate in the electrochemical reactions of the positive and negative electrodes. Therefore, alkaline nickel-zinc batteries have the characteristics of intrinsic safety and have broad application prospects in large-scale electrochemical energy storage, power batteries, emergency power supplies for data centers, backup power supplies, power tools, electric two-wheeled bicycles and other fields.
[0004] Since the active substance zinc oxide in the zinc electrode has a large solubility in the alkaline electrolyte, it can generate freely movable zincate ions Zn(OH)4 2- For example, at room temperature, the solubility of zinc oxide in a 30wt.% potassium hydroxide solution is about 54g / L, and in a 45wt.% potassium hydroxide solution, the solubility can be as high as 80g / L. Generally speaking, as the ambient temperature increases, the solubility of zinc oxide in potassium hydroxide solution will increase significantly. The chemical reaction that occurs during dissolution is as follows:
[0005] ZnO+H2O+2OH - →Zn(OH)4 2-
[0006] In addition, the zinc negative electrode of the nickel-zinc battery can also generate freely movable zincate ions during the charge and discharge process, which can easily cause deformation of the zinc negative electrode during the electrochemical deposition process, and even zinc dendrites cause battery short circuit, so that the zinc electrode exhibits a relatively short charge / discharge cycle life. In response to this technical problem, the existing technical solution includes adding various organic and / or inorganic additives to the zinc electrode and / or alkaline electrolyte to inhibit the dissolution of the zinc electrode discharge product in the alkaline electrolyte, so as to achieve the purpose of extending the cycle life of the alkaline nickel-zinc battery.
[0007] Commonly used additives in the prior art are insoluble inorganic calcium salts (including calcium hydroxide, calcium titanate, calcium oxide, etc.). For example, the zinc electrode uses nano zinc oxide and metallic zinc powder as the main negative electrode active materials, and insoluble calcium hydroxide (Ca(OH)2) is added to the zinc electrode as an additive during the manufacturing process of the zinc electrode. During the charge and discharge process of the alkaline nickel-zinc battery, the calcium hydroxide additive can combine with zinc oxide and the intermediate products of charge and discharge to form an insoluble phase called calcium zincate, and is identified by X-ray diffraction (XRD) as having the structural formula Ca[Zn(OH)3]2·2H2O. This relatively insoluble phase Ca[Zn(OH)3]2·2H2O can be quickly formed on the surface of the zinc electrode or inside the zinc electrode to avoid the loss of the negative electrode active material. On the one hand, by effectively inhibiting the solubility of the zinc oxide active material of the zinc electrode in the alkaline electrolyte, the zincate ion Zn(OH)4 2- The random diffusion in the alkaline electrolyte limits the electrochemical deposition reaction of zinc to a specific area. On the other hand, by anchoring the intermediate products generated by the zinc anode during the charge and discharge process, especially the zincate ion Zn(OH)4 2- , thereby limiting the discharge products of the zinc electrode to a specific area of the zinc electrode, which can effectively inhibit the deformation of the negative electrode and the growth of zinc dendrites to a certain extent, thereby achieving the purpose of extending the cycle life of the zinc electrode.
[0008] However, the additives commonly used in the prior art cannot achieve the expected results and cannot meet the requirements of the existing production and manufacturing processes. On the one hand, micron- or submicron-sized insoluble inorganic calcium salts (including calcium hydroxide, calcium titanate, calcium oxide, etc.) and negative electrode active materials (nano zinc oxide and micron metal zinc powder) exist in the form of particles in the negative electrode slurry. Due to the large differences in density and particle size of the particles, the mixing of the negative electrode slurry still has the problem of poor uniformity, which makes the soluble intermediate product Zn(OH)4 generated by the zinc electrode during the electrochemical process 2- The conversion reaction to calcium zincate becomes uneven. This shows that the added insoluble inorganic calcium salt has a significant effect on the conversion of Zn(OH)4 2- The anchoring effect is poor, and the calcium element inside it cannot bind to Zn(OH)4 2-There is an interaction between the two, and there is a problem of low utilization of calcium elements. It should be pointed out that additives such as calcium oxide will generate a lot of heat in the production process of negative electrode slurry, which not only consumes the water in the slurry, but also easily destroys the molecular structure and viscosity of the organic binder in the slurry, seriously affecting the slurry pulling or coating effect of the zinc negative electrode, making the quality control of the zinc electrode sheet more difficult. On the other hand, calcium hydroxide and calcium oxide, which are strongly alkaline, can easily react quickly with carbon dioxide in the air to generate calcium carbonate (CaCO3) particles during the actual preparation of negative electrode slurry. This will cause the negative electrode slurry to deteriorate easily, and even cause the softness of the zinc electrode to deteriorate. The hardening of the zinc electrode greatly increases the difficulty of actual battery cell winding, and the zinc negative electrode is prone to "fragmentation" problems. In addition, insoluble inorganic calcium salts with strong alkalinity (such as calcium hydroxide and calcium oxide) are not only prone to corrode iron production equipment, but also introduce trace impurity elements such as iron, nickel, and manganese in the production equipment into the zinc negative electrode, aggravating the hydrogen evolution side reaction of the zinc negative electrode during charging, which is not conducive to the performance of alkaline nickel-zinc batteries. Summary of the invention
[0009] The object of the present invention is to provide a zinc electrode for an alkaline nickel-zinc battery, wherein the electrochemical performance of the alkaline nickel-zinc battery using the zinc electrode is significantly improved.
[0010] The zinc electrode mainly includes active substances, aqueous binders, functional materials and current collectors. With the assistance of aqueous binders and thickeners, the active substances can be evenly coated on the surface or pores of the current collector to form a zinc electrode. The active substances mainly include nano zinc oxide and metal zinc powder, and can also include carbon-coated zinc oxide nanoparticles. In addition to binders and thickeners, functional materials can also include metal oxides, metal hydroxide additives and conductive agents. By introducing water-soluble organic acid calcium salts into the zinc electrode, under the action of alkaline electrolyte (potassium hydroxide, sodium hydroxide, lithium hydroxide), the surface of active substances such as nano zinc oxide or metal zinc powder of the zinc negative electrode can be in-situ coated to generate uniform calcium hydroxide, calcium zincate and their combinations. During the discharge process of alkaline nickel-zinc batteries, when zinc oxide or metallic zinc is converted into soluble intermediate zincate ions, it can immediately interact with the evenly distributed calcium element in the zinc electrode, and quickly generate electrochemically reversible, relatively insoluble calcium zincate phase (Ca(OH)2·2Zn(OH)2·xH2O, x=2 or 3) on the surface and specific areas inside the zinc electrode through in-situ coating, reducing the solubility of zinc oxide in alkaline electrolytes and solving the problem of random diffusion of zincate ions. It can achieve the effect of anchoring soluble intermediate products in specific areas, effectively reducing the deformation of the zinc electrode and inhibiting the growth of zinc dendrites. During the charge and discharge process, the calcium zincate in the zinc electrode can undergo reversible charge and discharge reactions according to the following reaction formula:
[0011]
[0012] During the charging process, calcium zincate can be electrochemically reduced to a mixture of metallic zinc and calcium hydroxide, which is uniformly present in the zinc electrode, wherein calcium hydroxide can be uniformly coated on the surface of active materials such as nano zinc oxide and metallic zinc, which not only effectively solves the dissolution problem of nano zinc oxide in alkaline electrolyte, but also effectively protects metallic zinc from corrosion in alkaline electrolyte environment; during the discharging process, the discharge product zincate ions formed after the oxidation of metallic zinc can react with calcium hydroxide at the original position to generate insoluble calcium zincate. Therefore, by in-situ anchoring of freely movable zincate ions through chemical interactions, not only the solubility of zinc oxide in alkaline electrolyte is effectively suppressed, but also the random diffusion problem of the discharge intermediate products (including zincate ions) of the zinc electrode is completely solved, thereby suppressing the problems of dendrite growth and negative electrode deformation of the zinc electrode, and the purpose of improving the discharge capacity of alkaline nickel-zinc batteries and extending the cycle life of zinc electrodes can be achieved.
[0013] It should be pointed out that since the evenly distributed calcium element in the zinc negative electrode can react chemically with the hydroxide ions in the alkaline electrolyte, the soluble organic calcium salt helps the hydroxide ions in the alkaline electrolyte to penetrate or infiltrate the zinc electrode, which is beneficial to improve the utilization rate of the negative electrode active material and enhance the discharge performance of the alkaline nickel-zinc battery.
[0014] The preparation method of the zinc electrode comprises the following steps:
[0015] The step of dissolving a water-soluble organic acid calcium salt in deionized water to obtain a first mixed solution;
[0016] The process of mixing a first mixed solution, a water-soluble binder, a thickener and an active material including zinc oxide to prepare a slurry;
[0017] The process of uniformly coating the slurry on the surface of the current collector and baking it at high temperature to prepare the zinc electrode.
[0018] In the slurry, preferably, based on the total weight of the water-soluble organic acid calcium salt, the aqueous binder, the thickener and the active material, the active material content is 80-97wt.%. Preferably, based on the total weight of the water-soluble organic acid calcium salt, the aqueous binder, the thickener and the active material, the total content of the water-soluble binder and the thickener is 1-5wt.%.
[0019] Among them, water-soluble organic acid calcium salts used in the present invention include calcium lactate, calcium acetate, calcium L-threonate, calcium gluconate, calcium benzoate, calcium glycerophosphate, calcium formate, calcium fumarate, calcium aspartate, calcium malate, calcium maleate, calcium propionate, calcium methanesulfonate, calcium trifluoromethanesulfonate, calcium mellitic acid, calcium p-toluenesulfonate and the like.
[0020] In one or more embodiments, the water-soluble organic acid calcium salt can be prepared using an insoluble inorganic calcium salt (such as calcium oxide, calcium hydroxide, calcium titanate, calcium carbonate, calcium bicarbonate, etc.) and an organic acid, wherein the organic acid is a water-soluble polyvalent carboxylic acid, such as citric acid, acetic acid, ethylenediaminetetraacetic acid, N-hydroxyethylenediaminetriacetic acid, nitrilotriacetic acid, 1,3-propylenediaminetetraacetic acid, succinic acid, fumaric acid, maleic acid, 1,2,3,4-cyclopentanetetraacetic acid, tartaric acid, glutamic acid, methanesulfonic acid, trifluoromethanesulfonic acid, mellitic acid, p-toluenesulfonic acid, etc.
[0021] The content of the water-soluble organic acid calcium salt in the first mixed solution is preferably 0.005-2 mol / L, more preferably 0.01-1.0 mol / L, and even more preferably 0.05-0.5 mol / L.
[0022] Among them, the pH value of the first mixed solution is preferably 6-8, more preferably 6.5-7.5, and even more preferably 6.8-7.2. When the pH value of the first mixed solution is greater than 8, it is easy to form calcium hydroxide or calcium carbonate in the subsequently prepared negative electrode slurry, thereby hardening the prepared zinc electrode, which is not conducive to the winding process of the battery cell. In one or more embodiments, the pH value of the first mixed solution is adjusted using the organic acid corresponding to the water-soluble organic acid calcium salt contained therein. When the pH value of the first mixed solution is less than 6, it is easy to cause the dissolution of the active substance zinc oxide and the corrosion of metallic zinc. In one or more embodiments, the pH value of the first mixed solution can also be adjusted using an alkaline solution.
[0023] Among them, when the zinc electrode is used as the negative electrode of the alkaline nickel-zinc battery, the following electrochemical reactions mainly occur during the charging and discharging process: during the charging process, the active substance zinc oxide of the zinc electrode gains electrons and is reduced to metallic zinc; during the discharging process, metallic zinc loses electrons and is oxidized to zinc oxide. It should be pointed out that during the electrochemical conversion reaction between zinc oxide and metallic zinc, a soluble intermediate product zincate ion Zn(OH)4 is easily generated. 2- In addition, zinc oxide and metallic zinc can also interact with alkaline substances such as potassium hydroxide, sodium hydroxide, and lithium hydroxide in alkaline electrolytes to generate soluble zincate ions. It can be seen that the electrochemical mutual conversion reaction between metallic zinc and zinc oxide mainly occurs at the zinc negative electrode, which is actually the electrochemical deposition of zinc and the dissolution reaction of zinc.
[0024] Charging process: ZnO+H2O+2e - →Zn+2OH -
[0025] Discharge process: Zn+2OH - →ZnO+H2O+2e-
[0026] Therefore, the active material of the zinc electrode, in addition to nano zinc oxide, can also include any form of metallic zinc, zinc compounds and zinc alloys. It should be pointed out that the composite material in which carbon is coated on the surface of zinc oxide or zinc compounds can be used as the active material of the zinc electrode. Mercury-free zinc alloy, as a zinc alloy, contains trace elements such as 0.01-0.06wt.% indium (In), 0.005-0.02wt.% bismuth (Bi), and 0.0035-0.015wt.% aluminum (Al), and has a good effect of inhibiting hydrogen evolution, so it is preferably used. In particular, indium (In) and bismuth (Bi) elements have a significant effect on improving the charge and discharge performance of alkaline nickel-zinc batteries. Using mercury-free zinc alloy as the active material of the zinc electrode can effectively alleviate the corrosion rate of the zinc electrode in the alkaline electrolyte on the one hand, and can also effectively inhibit the hydrogen evolution side reaction on the other hand, avoid the drying of the electrolyte or the "alkaline climbing" phenomenon of the alkaline nickel-zinc battery, and extend the cycle life of the nickel-zinc battery.
[0027] In one or more embodiments, the average particle size of zinc oxide in the active material is 100-400 nm.
[0028] In one or more embodiments, the average particle size of the metal zinc powder in the active material is 10-200 μm.
[0029] In one or more embodiments, the average particle size of the mercury-free zinc alloy is 10-200 μm.
[0030] Among them, the water-soluble binder is used to improve the binding properties of the active material particles to each other and the binding properties of the active material to the current collector. The water-soluble binder can be a rubber binder or a polymer resin binder. The rubber binder can be selected from styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber and a combination thereof. The polymer resin binder can be selected from polytetrafluoroethylene, ethylene propylene copolymer, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol and a combination thereof. The thickener can be sodium carboxymethyl cellulose, hydroxypropyl methylcellulose, methylcellulose, sodium alginate, β-cyclodextrin, sodium starch phosphate, hydroxypropyl starch, gelatin and xanthan gum and a combination thereof.
[0031] Wherein, the alkaline solution comprises any one or more of lithium hydroxide solution, sodium hydroxide solution and potassium hydroxide solution. Wherein, the mass ratio of potassium hydroxide, sodium hydroxide and lithium hydroxide is 10-30:1-10:1. The concentration of hydroxide ions is preferably 6-18 mol / L, more preferably 8-16 mol / L, and even more preferably 10-15 mol / L.
[0032] Among them, as examples of the current collector form, open-cell metal, expansion alloy, screen, inclined wire, foam, three-dimensional perforated foil, three-dimensional burr net, perforated foil and porous metal can be cited. As the material constituting the current collector, a metal with high conductivity and strong corrosion resistance is preferred, more preferably pure copper and copper alloy (such as brass, phosphor copper, etc.), most preferably pure copper. In addition, the surface of the current collector has good conductivity. Therefore, it can be a structure in which the surface is made of copper, tin, copper alloy or tin alloy and the interior is made of other materials such as zinc (Zn), aluminum (Al), antimony (Sb), bismuth (Bi), indium (In), titanium (Ti), etc., and the material inside is not limited to metal. The surface of the current collector can be plated with metals such as zinc (Zn), tin (Sn), indium (In), bismuth (Bi), aluminum (Al), silver (Ag) mercury (Hg), lead (Pb), etc., preferably tin-plated. According to such plating, the surface of the zinc electrode can be effectively suppressed from hydrogen evolution side reaction and the corrosion resistance of the current collector in an alkaline environment can be improved.
[0033] It should be pointed out that when an alkaline electrolyte containing potassium hydroxide, sodium hydroxide and lithium hydroxide is added to a battery cell consisting of a zinc negative electrode sheet and a Ni(OH)2 positive electrode sheet, the following chemical reactions mainly occur on the negative electrode sheet:
[0034]
[0035] From a thermodynamic point of view, the reaction can be carried out spontaneously inside the alkaline nickel-zinc battery. Among them, the surface of the active material (zinc oxide and zinc powder particles) of the zinc electrode will be in situ coated with calcium hydroxide, calcium zincate and their combination. In addition, the soluble zincate ions formed during the charge and discharge process can be effectively anchored in specific areas of the zinc electrode by the evenly distributed calcium element, avoiding the deformation of the zinc electrode and inhibiting the growth of zinc dendrites during the charge and discharge process.
[0036] In one or more embodiments, the active material for preparing the slurry may also be carbon-coated zinc oxide nanoparticles, carbon-coated zinc carbonate, carbon-coated calcium zincate, carbon-coated metallic zinc, and combinations thereof.
[0037] In one or more embodiments, when preparing the slurry, it is also necessary to add functional materials such as rare earth oxides, metal oxide additives, metal hydroxide additives, binders, thickeners, and conductive agents. As rare earth oxides, cerium dioxide, yttrium oxide, erbium oxide, dysprosium oxide, samarium oxide, gadolinium oxide, lanthanum trioxide, etc. can be cited. As oxide additives, magnesium oxide, mercuric oxide, lead oxide, barium oxide, aluminum oxide, bismuth oxide, indium oxide, boron oxide, and silicon dioxide can be cited. As hydroxide additives, bismuth hydroxide, indium hydroxide, barium hydroxide, magnesium hydroxide, and aluminum hydroxide can be cited. As examples of binders, polytetrafluoroethylene emulsions, styrene-butadiene rubber emulsions, polyvinyl alcohol and acrylonitrile multi-copolymer water-based binders can be cited. As examples of thickeners, sodium carboxymethyl cellulose, hydroxypropyl methylcellulose, methylcellulose, sodium alginate, β-cyclodextrin, sodium starch phosphate, hydroxypropyl starch, gelatin, and xanthan gum can be cited. Examples of conductive agents include metal tin powder, mercury-free zinc alloy powder, metal copper powder, metal indium powder, metal bismuth powder, metal titanium powder, metal antimony powder, metal tungsten powder, natural graphite, artificial graphite, carbon fiber, graphene, graphene oxide, carbon nanotubes, conductive carbon black and calcined organic polymer compounds.
[0038] In one or more embodiments, the zinc electrode after high-temperature baking is subjected to roller pressing to prevent the active material from falling off and to increase the compaction density of the zinc electrode.
[0039] In one or more embodiments, the zinc electrode is subjected to edge grinding to remove metal burrs generated during the metal mold or laser cutting process, thereby further avoiding a possible short circuit problem between the zinc electrode and the positive electrode.
[0040] In one or more embodiments, the zinc electrode is subjected to a softening treatment to improve the softness of the zinc electrode and further improve the penetration and wetting effect of the alkaline electrolyte into the zinc electrode.
[0041] In one or more embodiments, the zinc electrode needs to be welded with the tabs, and the tabs can be made of metal sheets such as copper sheets, zinc sheets, tinned copper sheets, zinc-copper alloys, etc., which have good conductivity, high alkali resistance, and high hydrogen evolution overpotential to improve electron transmission during charging and discharging.
[0042] It should be noted that the zinc electrode provided by the present invention can be applied not only to alkaline zinc-nickel batteries, but also to alkaline silver-zinc secondary batteries and alkaline zinc-manganese secondary batteries.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] 1. The zinc electrode prepared by the preparation method provided by the present invention can significantly improve the performance of alkaline nickel-zinc batteries, especially improve the utilization rate of zinc oxide active substances and the capacity retention rate during the cycle;
[0045] 2. The preparation method provided by the present invention can effectively improve the wettability of the zinc electrode to the alkaline electrolyte, which is mainly due to the interaction between the soluble calcium ions in the zinc electrode and the hydroxide ions in the alkaline electrolyte, which is conducive to promoting the rapid penetration and infiltration of hydroxide ions into the zinc electrode during the charge and discharge process;
[0046] 3. The water-soluble organic acid calcium salt provided by the present invention has a high solubility, which helps to evenly distribute calcium in the zinc electrode, effectively improves the utilization rate of calcium atoms, and further strengthens the anchoring effect between calcium and zinc oxide nanoparticles and charge-discharge intermediate products. By causing zinc electrodeposition and dissolution reactions in a specific area, the deformation of the zinc electrode can be minimized, and even the growth of zinc dendrites can be reduced, thereby extending the cycle life of the alkaline nickel-zinc battery.
[0047] 4. The preparation method provided by the present invention can be implemented on existing electrode preparation equipment. Since the negative electrode slurry is mild in nature and has no strong alkalinity and corrosiveness, it can not only avoid the "hardening" of the zinc electrode caused by calcium hydroxide or calcium carbonate produced during the preparation process, but also effectively avoid the introduction of impurity elements such as iron, nickel, and manganese in the equipment into the zinc electrode, which affects the performance of the alkaline nickel-zinc battery.
[0048] The following describes the invention in conjunction with specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The accompanying drawings further illustrate the present invention, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention.
[0050] Figure 1 The surface FE-SEM microstructure and EDS element distribution test results of the zinc electrode provided in Example 1 of the present invention ( Figure 1 a is the FE-SEM microstructure; Figure 1 b is the distribution of Zn element; Figure 1 c is the distribution of O element; Figure 1 d is the distribution of C element; Figure 1 e is the distribution of Ca element).
[0051] Figure 2 The surface FE-SEM microstructure and EDS element distribution test results of the zinc electrode provided in Example 2 of the present invention ( Figure 2 a is the FE-SEM microstructure; Figure 2 b is the distribution of Zn element; Figure 2 c is the distribution of O element; Figure 2 d is the distribution of C element; Figure 2 e is the distribution of Ca element).
[0052] Figure 3The surface FE-SEM microstructure and EDS element distribution test results of the zinc electrode provided in Example 3 of the present invention ( Figure 3 a is the FE-SEM microstructure; Figure 3 b is the distribution of Zn element; Figure 3 c is the distribution of O element; Figure 3 d is the distribution of C element; Figure 3 e is the distribution of Ca element).
[0053] Figure 4 The contact angle test results of zinc electrode ( Figure 4 a is the zinc electrode provided in Example 3 of the present invention; Figure 4 b is the zinc electrode provided in Comparative Example 1 of the present invention).
[0054] Figure 5 The performance test results of the CR2032 button battery prepared using the zinc electrode provided in Example 1 of the present invention ( Figure 5 a is the cycle performance data; Figure 5 b is the data of the discharge platform, Figure 5 c is the charge and discharge curve for the first 5 cycles).
[0055] Figure 6 The performance test results of the CR2032 button battery prepared using the zinc electrode provided in Example 2 of the present invention ( Figure 6 a is the cycle performance data; Figure 6 b is the data of the discharge platform, Figure 6 c is the charge and discharge curve for the first 5 cycles).
[0056] Figure 7 The performance test results of the CR2032 button battery prepared using the zinc electrode provided in Example 3 of the present invention ( Figure 7 a is the cycle performance data; Figure 7 b is the data of the discharge platform; Figure 7 c is the charge and discharge curve for the first 5 cycles).
[0057] Figure 8 The performance test results of the CR2032 button battery prepared by the zinc electrode provided in Comparative Example 1 of the present invention are shown in FIG. Figure 8 a is the cycle performance data; Figure 8 b is the data of the discharge platform; Figure 8 c is the charge and discharge curve for the first 5 cycles). DETAILED DESCRIPTION
[0058] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0059] The zinc electrode provided by the embodiment of the present invention can be applied to alkaline nickel-zinc batteries as the negative electrode of the alkaline nickel-zinc batteries.
[0060] [Alkaline nickel-zinc battery]
[0061] The alkaline nickel-zinc battery includes a sealed container, in which there are a positive electrode, an electrolyte, a negative electrode and a separator.
[0062] [positive electrode]
[0063] The positive electrode includes a positive electrode active material and a positive electrode current collector, and the positive electrode active material includes nickel hydroxide and / or nickel oxyhydroxide. Nickel hydroxide usually presents spherical particles, and doping elements other than nickel can be dissolved in its lattice, which helps to improve the cycle performance of alkaline nickel-zinc batteries and higher coulomb efficiency at high temperatures. As examples of doping elements, elements such as zinc (Zn), cobalt (Co), aluminum (Al), magnesium (Mg), tungsten (W), titanium (Ti), barium (Ba), and zirconium (Zr) can be listed. Cobalt compounds can be directly added to the nickel hydroxide active material for use. As examples of such cobalt compounds, metal cobalt powder, cobaltous oxide, cobalt trioxide, cobalt tetraoxide, and any combination thereof can be listed. In addition, the spherical nickel hydroxide particles, especially the positive electrode materials dissolved with doping elements, can also be surface coated with cobalt compounds. As examples of such cobalt compounds, cobaltous oxide, α-type cobalt hydroxide, β-type cobalt hydroxide, compounds of high-valent cobalt exceeding 2 valences, and any combination thereof can be listed.
[0064] The positive electrode active material may further include additional elements in addition to the nickel hydroxide compound and the doping element that can be dissolved in the nickel hydroxide compound. Examples of such additional elements include scandium (Sc), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), lutetium (Lu), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), gold (Au), mercury (Hg) and any combination thereof. The form of the additional element is not particularly limited, and may be present in the form of a metal element or a metal compound (e.g., oxide, hydroxide, nitride, sulfide, carbide, halide and carbonate). The amount of the metal single substance or metal compound of the additional element added is preferably 0.5 to 20 parts by weight, more preferably 1 to 5 parts by weight, based on 100 parts by weight of the nickel hydroxide-based compound.
[0065] The positive electrode may also contain a conductive material, a binder and a thickener as required. Among them, the conductive material can be listed as: graphite, graphene, graphene oxide, carbon black, metal nickel powder, metal tungsten powder, metal cobalt powder, etc. The binder and thickener can be listed as: polyvinylidene fluoride, polyvinyl alcohol, hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, sodium polyacrylate, polystyrene butadiene copolymer, polytetrafluoroethylene, etc.
[0066] The positive electrode can also be prepared using a dry process or a wet process as required, and the positive electrode active material, the conductive agent, the binder, etc. can be fully premixed during the preparation process.
[0067] As a preferred example of the positive electrode current collector, a nickel porous substrate such as a foamed nickel plate can be cited. In this case, for example, it is preferred to uniformly apply a positive electrode slurry containing an active material such as nickel hydroxide on a nickel porous substrate and dry it to make a positive electrode formed by a positive electrode active material and a positive electrode current collector. At this time, it is also preferred to perform a roller pressing process on the dried positive electrode to prevent the positive electrode active material from falling off and to increase the compaction density of the electrode. It is also preferred to perform an edge grinding process on the dried positive electrode to reduce the risk of battery short circuit by removing possible metal burrs. It is also preferred to perform a sheet kneading process on the dried positive electrode, which not only avoids the breakage of the electrode sheet during the winding process of the battery cell by improving the softness of the positive electrode sheet, but also helps the alkaline electrolyte to quickly penetrate into the positive electrode sheet.
[0068] [Electrolyte]
[0069] The electrolyte contains an alkali metal hydroxide. An aqueous solution containing an alkali metal hydroxide is used as an electrolyte for an alkaline nickel-zinc battery. Examples of alkali metal hydroxides include potassium hydroxide, sodium hydroxide, lithium hydroxide, and the like. The mass ratio of potassium hydroxide, sodium hydroxide, and lithium hydroxide is 10-30:1-10:1. In order to inhibit the corrosion of zinc in an alkaline environment, compounds such as zinc oxide, zinc hydroxide, fumed silica, and aluminum hydroxide may be added to the alkaline electrolyte. In order to inhibit the precipitation of gas during the charge and discharge process, trace or trace amounts of indium (In), bismuth (Bi), tin (Sn), lead (Pb), magnesium (Mg), barium (Ba), calcium (Ca), aluminum (Al), mercury (Hg), and lead (Pb) may be added to the alkaline electrolyte. For example: hydroxides, sulfides, halides, nitrates, nitrites, sulfates, phosphates, pyrophosphates, polyphosphates, and any combination thereof. In order to inhibit the deformation of the zinc negative electrode, soluble organic calcium salts, zinc oxide, and calcium hydroxide may be added to the alkaline electrolyte. Examples of the soluble organic calcium salt include at least one of calcium lactate, calcium acetate, calcium L-threonate, calcium gluconate, calcium benzoate, calcium glycerophosphate, calcium formate, calcium fumarate, calcium aspartate, calcium malate, calcium maleate, calcium propionate, calcium methanesulfonate, calcium trifluoromethanesulfonate, calcium mellitic acid, and calcium p-toluenesulfonate.
[0070] The preferred concentration of alkali metal hydroxide in the electrolyte is 6-18 mol / L, more preferably 8-16 mol / L, and even more preferably 10-15 mol / L. A higher hydroxide ion concentration in the alkaline electrolyte can not only improve the ionic conductivity of the electrolyte, reduce the internal resistance of the alkaline nickel-zinc battery, and improve the rate performance of the alkaline nickel-zinc battery, but also promote the participation of soluble organic calcium salts in the in-situ coating reaction on the surface of the active material, effectively inhibit the deformation of the zinc electrode, and extend the cycle life of the alkaline nickel-zinc battery.
[0071] [Diaphragm]
[0072] The diaphragm is a component between the nickel hydroxide positive electrode and the zinc negative electrode, which keeps the positive electrode and the negative electrode insulated and can conduct hydroxide ions. As a diaphragm, for example, a porous film made of resin, a non-woven fabric made of resin, etc. can be used. As examples of resins, polyolefins, fluorine-based polymers, cellulose-based polymers, polyimides, nylons, etc. can be cited. The diaphragm can be a single-layer structure or a stacked structure of more than two layers. For example: a three-layer composite structure in which a polyethylene (PE) plastic layer is stacked on both sides with a polypropylene (PP) plastic layer, and the composite method can be composited by water-soluble glue or hot pressing technology. The diaphragm of the alkaline nickel-zinc battery has a strong electrolyte absorption capacity and can solve the short-circuit problem caused by zinc dendrites. In order to further improve the hydrophilicity and liquid absorption properties of the diaphragm, the surface of the non-woven diaphragm can be grafted or sulfonated. In order to avoid short circuits caused by zinc dendrites, the pore size range of the diaphragm needs to be controlled within 10-80nm. In order to improve the thermal stability of the separator, a separator may be used in which an oxide such as zinc oxide, silicon dioxide, aluminum oxide, titanium dioxide, or magnesium oxide and / or a nitride such as aluminum nitride, silicon nitride, or boron nitride is coated on a porous substrate.
[0073] [Example 1]
[0074] This embodiment provides a zinc electrode, and the preparation method of the zinc electrode comprises the following steps:
[0075] Step 1, dissolving calcium lactate in deionized water to obtain a first mixed solution, wherein the content of calcium ions in the first mixed solution is 0.1 mol / L;
[0076] Step 2: Mix the first mixed solution, carbon-coated zinc oxide particles (average particle size: 100-400 nm), zinc powder particles, styrene-butadiene rubber, and sodium carboxymethyl cellulose, and fully stir in a universal mixer to obtain a uniformly dispersed negative electrode slurry, wherein the mass ratio of calcium lactate, carbon-coated zinc oxide particles, zinc powder particles, styrene-butadiene rubber, and sodium carboxymethyl cellulose is 1:90:7:1:1;
[0077] Step 3: Use 25 μm thick tinned copper foil as the current collector. According to conventional methods, 10 mg / cm 2 The negative electrode slurry was evenly coated on the surface of the current collector with a coating amount of , and then vacuum high-temperature baking was performed at 160°C for 30 minutes.
[0078] Step 4: Roll-press the dried electrode with a rolling tonnage of 35 tons to obtain a zinc electrode.
[0079] [Example 2]
[0080] This embodiment provides a zinc electrode, and the preparation method of the zinc electrode comprises the following steps:
[0081] Step 1, dissolving calcium L-threonate in deionized water to obtain a first mixed solution, wherein the content of calcium L-threonate in the first mixed solution is 0.05 mol / L;
[0082] Step 2, mixing the first mixed solution, carbon-coated zinc oxide particles (average particle size: 100-400 nm), zinc powder particles, styrene-butadiene rubber, and sodium carboxymethyl cellulose, and fully stirring in a universal mixer to obtain a uniformly dispersed negative electrode slurry, wherein the mass ratio of L-threonate calcium, carbon-coated zinc oxide particles, zinc powder particles, styrene-butadiene rubber, and sodium carboxymethyl cellulose is 1:90:7:1:1;
[0083] Step 3: Use 25 μm thick tinned copper foil as the current collector. According to the conventional method, 8 mg / cm 2 The negative electrode slurry was evenly coated on the surface of the current collector with a coating amount of , and then vacuum high-temperature baking was performed at 150°C for 1 hour.
[0084] Step 4: Roll-press the dried electrode with a rolling tonnage of 35 tons to obtain a zinc electrode.
[0085] [Example 3]
[0086] This embodiment provides a zinc electrode, and the preparation method of the zinc electrode comprises the following steps:
[0087] Step 1, dissolving calcium acetate in deionized water to obtain a first mixed solution, wherein the content of calcium acetate in the first mixed solution is 0.1 mol / L;
[0088] Step 2: Mix the first mixed solution, carbon-coated zinc oxide particles (average particle size: 100-400 nm), zinc powder particles, styrene-butadiene rubber, and sodium carboxymethyl cellulose, and fully stir in a universal mixer to obtain a uniformly dispersed negative electrode slurry, wherein the mass ratio of calcium acetate, carbon-coated zinc oxide particles, zinc powder particles, styrene-butadiene rubber, and sodium carboxymethyl cellulose is 1:87:10:1:1;
[0089] Step 3: Use 20 μm thick tinned copper foil as the current collector. According to the conventional method, 12 mg / cm 2 The negative electrode slurry is evenly coated on the surface of the current collector with a coating amount of , and then vacuum high-temperature baking is performed at 180°C for 30 minutes.
[0090] Step 4: Roll-press the dried electrode with a rolling tonnage of 35 tons to obtain a zinc electrode.
[0091] [Comparative Example 1]
[0092] The only difference between this comparative example and Example 1 is that calcium lactate is not used in preparing the zinc electrode.
[0093] Step 1: Carbon-coated zinc oxide particles (average particle size: 100-400 nm), zinc powder particles, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 90:8:1:1, and fully stirred in a universal mixer to obtain a uniformly dispersed negative electrode slurry;
[0094] Step 2: Use 25 μm thick tinned copper foil as the current collector. According to conventional methods, 10 mg / cm 2 The negative electrode slurry was evenly coated on the surface of the current collector with a coating amount of , and then vacuum high-temperature baking was performed at 160°C for 30 minutes.
[0095] Step three, rolling the dried electrode sheet with a rolling tonnage of 35 tons to obtain a zinc electrode.
[0096] [Comparative Example 2]
[0097] This comparative example provides a zinc electrode, and the preparation method of the zinc electrode comprises the following steps:
[0098] Step 1: Mix calcium hydroxide and deionized water to obtain a first suspension, wherein 7.41 g of calcium hydroxide is contained per 1 L of deionized water;
[0099] Step 2, mixing the first mixed solution, carbon-coated zinc oxide particles (average particle size: 100-400 nm), zinc powder particles, styrene-butadiene rubber and sodium carboxymethyl cellulose, and fully stirring in a universal mixer to obtain a uniformly dispersed negative electrode slurry, wherein the mass ratio of calcium hydroxide, carbon-coated zinc oxide particles, zinc powder particles, styrene-butadiene rubber and sodium carboxymethyl cellulose is 1:90:7:1:1;
[0100] Step 3: Use 25 μm thick tinned copper foil as the current collector. According to conventional methods, 10 mg / cm 2 The negative electrode slurry was evenly coated on the surface of the current collector with a coating amount of , and then vacuum high-temperature baking was performed at 150°C for 1 hour.
[0101] Step 4: Roll-press the dried electrode with a rolling tonnage of 35 tons to obtain a zinc electrode.
[0102] [Comparative Example 3]
[0103] This comparative example provides a zinc electrode, and the preparation method of the zinc electrode comprises the following steps:
[0104] Step 1, dissolving acetic acid in deionized water to obtain a first mixed solution, wherein the content of acetic acid in the first mixed solution is 0.1 mol / L;
[0105] Step 2: Mix the first mixed solution, the carbon-coated zinc oxide particles (average particle size: 100-400 nm), the zinc powder particles, styrene-butadiene rubber and sodium carboxymethyl cellulose, wherein the mass ratio of acetic acid, carbon-coated zinc oxide particles, zinc powder particles, styrene-butadiene rubber and sodium carboxymethyl cellulose is 1:87:10:1:1, and stir them in a universal mixer to obtain a uniformly dispersed negative electrode slurry;
[0106] Step 3: Use 0.5 mol / L sodium hydroxide solution to adjust the pH of the negative electrode slurry to 7.2, and use 10 μm thick tin-plated copper foil as the current collector. According to the conventional method, 22 mg / cm 2 The negative electrode slurry is coated on the surface of the copper foil with a coating amount of , and then vacuum high-temperature baking is performed at 140°C for 10 hours;
[0107] Step 4: Roll the dried electrode sheet with a rolling tonnage of 35T to obtain a zinc electrode. Current collector.
[0108] [Comparative Example 4]
[0109] This comparative example provides a zinc electrode, and the preparation method of the zinc electrode comprises the following steps:
[0110] Step 1, placing calcium hydroxide particles and zinc oxide particles with an average particle size of 100-400 nm into a ball milling tank of a planetary ball mill;
[0111] Step 2, adding stainless steel balls to a ball mill at a mass ratio of 4:1 between balls and materials, and then adding deionized water, and ball milling at a speed of 300 rpm under argon protection, taking out the product after ball milling for 15 hours, and baking at 50° C. for 12 hours to obtain a first mixture;
[0112] Step 3, deionized water, the first mixture, zinc powder particles, styrene-butadiene rubber, and sodium carboxymethyl cellulose are fully stirred in a universal mixer until a uniformly dispersed negative electrode slurry is obtained, wherein the mass ratio of calcium hydroxide, zinc oxide particles, zinc powder particles, styrene-butadiene rubber, and sodium carboxymethyl cellulose is 1:90:7:1:1, and a 0.5 mol / L sodium hydroxide solution is used to adjust the pH of the slurry to 7.2;
[0113] Step 4: Use 10 μm thick tinned copper foil as the current collector. According to conventional methods, 22 mg / cm 2 The slurry was coated on the surface of the copper foil with a coating amount of , and then vacuum high-temperature baking was carried out at 140°C for 10 hours to obtain a zinc electrode.
[0114] [Comparative test]
[0115] The zinc electrodes prepared in Examples 1-3 were observed using a field emission scanning electron microscope (FE-SEM), and the element distribution of the observed area was tested using an X-ray energy dispersive spectrometer (EDS). Figure 1-3 As shown, the calcium element of the zinc electrode prepared by the preparation method of Examples 1-3 is well evenly distributed. On the one hand, the evenly distributed calcium element is beneficial to reducing the solubility of zinc oxide in alkaline electrolyte and inhibiting the diffusion of zincate ions in the electrolyte, improving the deformation of the zinc electrode and inhibiting the growth of zinc dendrites. On the other hand, the evenly distributed calcium element helps to effectively anchor the zincate ions formed during the charge and discharge process of the alkaline nickel-zinc battery, forming a relatively insoluble phase of calcium zincate on the surface or specific internal area of the zinc electrode, thereby improving the cycle performance of the alkaline nickel-zinc battery.
[0116] It should be pointed out that if Figure 1 a, Figure 2 a and Figure 2 As shown in c, the surface FE-SEM microscopic test results of the zinc electrode show that the zinc negative electrode is mainly composed of 100-400nm carbon-coated nano zinc oxide particles. In addition, the EDS element distribution test can clearly show the uniform distribution of Zn, O, C and Ca elements. Figure 1 b, Figure 2 b and Figure 3 As shown in b, the Zn element is evenly distributed, mainly coming from the active material zinc oxide or metallic zinc; Figure 1 c, Figure 2 c and Figure 3 As shown in c, the O element is evenly distributed and mainly comes from the active substance zinc oxide; Figure 1 d, Figure 2 d and Figure 3 As shown in Figure d, the C element is evenly distributed and mainly comes from the carbon coating layer, aqueous binder and thickener; Figure 1 e, Figure 2 e and Figure 3 As shown in Figure e, the Ca element is evenly distributed, mainly from soluble organic calcium salts. If an insoluble inorganic calcium salt is used, the distribution of the Ca element is relatively concentrated, mainly affected by its particle size and solubility. The uniform distribution of the Ca element in the zinc electrodes prepared in Examples 1-3 of the present invention is mainly related to its presence in the form of calcium ions in the negative electrode slurry.
[0117] The zinc electrodes prepared in Examples 1-3 and the zinc electrodes prepared in Comparative Examples 1-4 were subjected to contact angle tests on alkaline electrolytes. The contact angle test was conducted in an environment with a temperature of 20-25°C and a humidity of ≤50% RH. 1 μL of alkaline electrolyte was dripped onto the surface of the zinc electrode through a plastic dropper. The smaller the angle between the test liquid surface and the zinc electrode, the more sufficient the alkaline electrolyte infiltration. The better the wettability of the zinc electrode with the alkaline electrolyte, the more conducive it is to improving the performance of the alkaline nickel-zinc battery. See Table 1 for the contact angle test results.
[0118] It should be pointed out that soluble organic calcium salts can greatly improve the wettability of zinc electrodes to alkaline electrolytes. Figure 4 As shown, by comparing Example 3 ( Figure 4 a) and Comparative Example 1 ( Figure 4 b) When a soluble organic calcium salt (calcium acetate) is added, the contact angle between the zinc electrode and the alkaline electrolyte is 73.2°, which is significantly lower than that of the zinc electrode without the addition of organic calcium salt (83.6°). This is mainly related to the uniform distribution of the soluble organic calcium salt in the zinc electrode. The calcium ions in the soluble organic calcium salt can react chemically with the hydroxide ions in the alkaline electrolyte, and can generate calcium hydroxide or calcium zincate in situ inside the alkaline nickel-zinc battery to coat the surface of the active material zinc oxide and zinc powder. This can not only promote the penetration of the alkaline electrolyte into the interior of the zinc negative electrode, but also reduce the solubility of zinc oxide in the alkaline electrolyte and solve the problem of the random diffusion of zincate ions generated during the charge and discharge process in the alkaline electrolyte.
[0119] [Method for manufacturing alkaline nickel-zinc battery]
[0120] The zinc electrodes prepared in Examples 1-3 and the zinc electrodes prepared in Comparative Examples 1-4 were respectively used to prepare alkaline nickel-zinc batteries, and the specific preparation methods are as follows:
[0121] Step 1: By using the metal plate drawing method, nickel plating and tin plating are used on the surface of the iron substrate to prepare the positive electrode steel shell and negative electrode steel shell of the standard CR2032 button battery respectively.
[0122] Step 2: Use foamed nickel as the positive electrode current collector, and fill the foamed nickel with a positive electrode active material, a conductive agent, and a binder to prepare the positive electrode. The positive electrode mainly includes: nickel hydroxide, metallic nickel, yttrium oxide, polytetrafluoroethylene, and carboxymethyl cellulose. Among them, the mass ratio of nickel hydroxide, metallic nickel, yttrium oxide, polytetrafluoroethylene, and carboxymethyl cellulose is 92:2:2:2:2. In addition, the coating amount of the positive electrode is about 200 mg / cm 2 The thickness of the positive electrode is about 300μm and the diameter of the positive electrode is 15mm.
[0123] Step 3, respectively cutting the zinc electrodes prepared in Examples 1-3 and Comparative Examples 1-4 into zinc electrode sheets with a diameter of 14 mm;
[0124] Step 4, use a composite water-based diaphragm with a thickness of about 120μm and a diameter of about 16mm. Among them, the thickness of the non-woven fabric with strong liquid absorption ability is about 100μm, and the thickness of the microporous diaphragm with anti-dendrite function is about 20μm. The way to place the composite water-based diaphragm between the positive electrode and the zinc electrode plate is to stack the positive electrode, diaphragm and zinc electrode plate in sequence, and then inject and seal, and store it in a standard CR2032 button battery container. For alkaline electrolyte, the concentration of hydroxide ions is about 12mol / L.
[0125] The prepared alkaline nickel-zinc button battery was subjected to the following performance tests.
[0126] [Charge and discharge cycle test]
[0127] The following charge and discharge cycle tests were performed on alkaline nickel-zinc button batteries using the Xinwei battery testing system.
[0128] As the first charge and discharge cycle, the alkaline nickel-zinc button battery prepared above was charged at a constant current of 1 / 10C to 1.9V, then charged at a constant voltage of 1.9V to a current cutoff of 0.1C, and finally discharged at a constant current of 1 / 2C to 1.2V.
[0129] Next, as the second charge and discharge cycle, the nickel-zinc battery prepared above was charged at a constant current of 1 / 5C to 1.9V, then charged at a constant voltage of 1.9V to 0.1C current cutoff, and finally discharged at a constant current of 1 / 2C to 1.2V.
[0130] Thereafter, as the third charge-discharge cycle, the nickel-zinc battery prepared above was charged at a constant current of 1 / 2C to 1.9V, then charged at a constant voltage of 1.9V to a current cutoff of 0.1C, and finally discharged at a constant current of 1 / 2C to 1.2V.
[0131] Thereafter, the third charge and discharge procedure was repeated, and a maximum of 100 charge and discharge cycles were performed.
[0132] The capacity retention rate (%) is calculated using the discharge capacity in grams during the first charge-discharge cycle and the discharge capacity in grams at the predetermined number of cycles. In addition, based on the theoretical discharge capacity in grams of zinc oxide of 658 mAh / g, the actual discharge capacity in grams of zinc oxide is divided by the theoretical capacity in grams of zinc oxide of 658 mAh / g to calculate the utilization rate of the zinc oxide active material in the alkaline nickel-zinc battery. The results are shown in Table 1.
[0133] As shown in the results of Table 1, the zinc electrodes provided by Examples 1-3 of the present invention have better first discharge gram capacity, utilization rate of zinc oxide and capacity retention rate than the comparative examples provided by the present invention. By adding soluble organic calcium salts to the zinc electrode, not only the dissolution problem of zinc oxide active material in alkaline electrolyte is overcome, but also the random diffusion of intermediate zincate ions formed during the charge and discharge process can be effectively suppressed. By improving the deformation of the zinc electrode and suppressing the growth of zinc dendrites, the cycle stability of the alkaline nickel-zinc battery and the utilization rate of the active material are significantly improved.
[0134] In addition, soluble organic calcium salts contribute to the penetration and wetting of alkaline electrolytes, and the electrolyte wetting angle of the zinc electrodes provided in Examples 1-3 of the present invention is significantly smaller than that of the comparative examples provided by the present invention. Excellent electrolyte wettability helps to improve the utilization rate of the active substance zinc oxide. Generally speaking, zinc oxide, as an important active substance in the negative electrode of alkaline nickel-zinc batteries, has a theoretical gram capacity of 658 mAh / g. The utilization rate of active materials in existing alkaline nickel-zinc battery technology is only 20-30%. Therefore, in the design process of alkaline nickel-zinc batteries, the amount of negative electrode active material needs to be much higher than its theoretical design value, and the theoretical capacity of the negative electrode can even reach more than twice the capacity of the positive electrode. Comparative Example 1 of the present invention uses carbon-coated zinc oxide, and the utilization rate of active materials can be increased to 64%. By adding soluble organic calcium salts to the zinc electrode, the zinc electrode provided in Examples 1-3 of the present invention can show an active material utilization rate of 73%-88% during the charge and discharge process, which helps to further improve the mass energy density of the battery.
[0135] It should be pointed out that the capacity retention rate of the zinc electrode provided in Examples 1-3 of the present invention after 100 cycles of charge and discharge is significantly better than that of the zinc electrode provided in the comparative example of the present invention. In particular, in Example 3 of the present invention, after the zinc electrode has been cycled 100 times, the discharge gram capacity remains basically stable. By limiting the activity of soluble zincate ions in specific areas, it is prevented from randomly diffusing into alkaline electrolytes, diaphragms, and even the surface of the positive electrode. The zinc electrodes provided in Examples 1-3 of the present invention can achieve a higher capacity retention rate by alleviating the loss of zinc oxide active substances in the zinc electrode.
[0136] Table 1
[0137]
[0138] In order to further illustrate the effect of soluble organic calcium salt, the prepared alkaline nickel-zinc button battery CR2032 was subjected to cycle testing using the Xinwei battery testing system.
[0139] Regarding the discharge gram capacity of the active material zinc oxide, such as Figure 5 a, Figure 6 a, Figure 7 a and Figure 8 As shown in a, the zinc electrodes provided in Examples 1-3 of the present invention and Comparative Example 1 are charged and discharged for 100 cycles in a nickel-zinc button battery CR2032. The first cycle discharge capacity of the zinc electrode provided in Example 1 of the present invention is 481mAh / g, and after 100 cycles of charge and discharge, its discharge capacity is 454mAh / g, and the capacity retention rate is 94%; the first cycle discharge capacity of the zinc electrode provided in Example 2 of the present invention is 513mAh / g, and after 100 cycles of charge and discharge, its discharge capacity is 423mAh / g, and the capacity retention rate is 82%; the first cycle discharge capacity of the zinc electrode provided in Example 3 of the present invention is 582mAh / g, and after 100 cycles of charge and discharge, its discharge capacity is 591mAh / g, and there is no obvious decline in the discharge capacity. However, the first cycle discharge capacity of the zinc electrode provided in Comparative Example 1 of the present invention is 422mAh / g, and after 100 cycles of charge and discharge, its discharge capacity is 338mAh / g, and the capacity retention rate is 80%.
[0140] For the discharge platform, such as Figure 5 b, Figure 6 b, Figure 7 b and Figure 8As shown in Figure 2, the zinc electrodes provided in Examples 1-3 of the present invention and Comparative Example 1 are placed in a nickel-zinc button cell CR2032, and the discharge platform is basically maintained at ~1.7V after 100 cycles of charge and discharge. Usually, a zinc electrode prepared from pure zinc oxide can exhibit a discharge platform of 1.60-1.65V. The zinc electrodes provided in Examples 1-3 of the present invention and Comparative Example 1 use carbon-coated zinc oxide active materials, which can exhibit a higher discharge platform and help improve the mass energy density of alkaline nickel-zinc batteries. It can be seen that soluble organic calcium salts have no effect on the discharge platform of alkaline nickel-zinc batteries.
[0141] For the charge and discharge curve, such as Figure 5 c, Figure 6 c, Figure 7 c and Figure 8 As shown in Figure c, the first five charge and discharge curves of the zinc electrodes provided by Examples 1-3 of the present invention and Comparative Example 1 in the nickel-zinc button battery CR2032 are basically overlapped, indicating good electrochemical reversibility and charge and discharge stability. It should be pointed out that the initial discharge capacity is slightly improved, which is mainly related to the need for further activation of the alkaline nickel-zinc button battery in the initial charge and discharge process.
[0142] It should be noted that for different soluble organic calcium salts, the cation is a calcium ion and the anion can be an organic group with different molecular weights. By further optimizing the amount of the soluble organic calcium salt provided by the present invention added to the zinc electrode, the overall performance of the alkaline nickel-zinc battery can be further optimized and improved.
[0143] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0144] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a zinc electrode, characterized in that: Including the following processes: The step of dissolving a water-soluble organic acid calcium salt in deionized water to obtain a first mixed solution; The process of preparing a slurry by mixing a first mixed liquid, an aqueous binder, a thickener and an active material including zinc oxide; The process of coating the slurry on the surface of the current collector and baking at high temperature to prepare the zinc electrode.
2. The preparation method according to claim 1, characterized in that: The content of water-soluble organic acid calcium salt in the first mixed solution is 0.005-2 mol / L.
3. The preparation method according to claim 2, characterized in that: The pH value of the first mixed solution is 6-8.
4. The preparation method according to claim 3, characterized in that: The water-soluble organic acid calcium salt is at least one of calcium lactate, calcium acetate, calcium L-threonate, calcium gluconate, calcium benzoate, calcium glycerophosphate, calcium formate, calcium fumarate, calcium caseinate, calcium aspartate, calcium maleate, calcium propionate, calcium methanesulfonate, calcium trifluoromethanesulfonate, calcium mellitic acid, and calcium p-toluenesulfonate.
5. The preparation method according to claim 1, characterized in that: Based on the total weight of the water-soluble organic acid calcium salt, the aqueous binder, the thickener and the active material, the active material content is 80 wt.% to 97 wt.%; The total content of the water-soluble organic acid calcium salt, the aqueous binder, the thickener and the active material is 1 wt.% to 5 wt.% based on the total weight of the water-soluble organic acid calcium salt, the aqueous binder, the thickener and the active material.
6. The preparation method according to claim 5, characterized in that: The water-soluble adhesive is a rubber adhesive or a polymer resin adhesive.
7. The preparation method according to claim 6, characterized in that: The rubber adhesive is at least one of styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, and fluororubber; The polymer resin binder is at least one of polytetrafluoroethylene, ethylene propylene copolymer, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, and polyvinyl alcohol; The thickener is at least one of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, sodium alginate, β-cyclodextrin, sodium starch phosphate, hydroxypropyl starch, gelatin, and xanthan gum.
8. The preparation method according to claim 1, characterized in that: The temperature of the high temperature baking is 100-180° C., and the time of the high temperature baking is 5 min-5 h.
9. A zinc electrode prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the zinc electrode according to claim 9 in an alkaline nickel-zinc battery.
Citation Information
Patent Citations
Zinc electrode and alkaline secondary cell including the same
CN101136470A
Sealed zinc-nickel secondary cell zinc negative electrode, and cell and preparation method thereof
CN103280559A
Shell and nickel-zinc battery using same
CN218957862U
Manufacture of zinc electrode for alkaline storage battery
JP1988019767A
Zinc negative electrode mixture, and battery arranged by use thereof
JP2014026951A